“Study On Trend Analysis And Financial Performance Of Selected Public Sector Banks In India” (International Journal of Food and Nutritional Sciences, 2022)
Banking as a major part of the financial sector, is the life blood of the economy. It plays a decisive role in accelerating the rate of economic growth. The importance of commercial banks in the process of economic development has been stressed from time to time by the economic thinkers and progressive bankers in the country. Banks are the heart of our financial structure. Banks play a positive role in the economic development of a nation as depositories of community’s savings and as purveyors of credit. Indian banks have aided the economic development during the past fifty-eight years in an effective way. The banking sector has shown remarkable responsiveness to the needs of planned economy. The purpose of the study is to understand trend analysis and financial performance of selected SBI and BOB public sector banks in India. The period of study would be ten years during 2010-11 to 2019-20.